Social-cultural factors influencing modern contraceptive uptake among women of the reproductive age in Turkana County, Kenya - Okenyoru, Douglas S.; Matoke, Vincent; Odhiambo, Felix; Salima, Ruth; Anyika, Daniel; Ogutu, Gideon (International Journal Of Community Medicine And Public Health, 2023)
Background: Modern contraceptive is pivotal for reproductive health, averting unplanned pregnancies, lowering maternal mortality, and enhancing women’s well-being. Despite global strides, challenges still persist in adoption of modern family planning methods in regions, like Turkana County, Kenya with a 30.7% adoption rate marking high unmet contraception needs. This study delved into determining social-cultural factors impacting uptake of modern contraceptive in the remote area of Turkana, Kenya. Methods: A descriptive cross-sectional study was employed. The 360 participants were sampled from households using systematic random sampling. Data was analyzed using SPSS 21.0. Data analysis included frequencies, proportions and Chi-square tests to unveil vital variable correlations. Data was presented in tables, graphs and pie charts. Results: The study revealed higher utilization of modern contraceptives at 53%. Cultural factors associated with Modern contraceptive uptake included religion acceptance of family planning (χ2=6.997, p=0.008), myths and misconceptions (χ2=31.096, p=0.000), gender preference (χ2=28.876, p=0.000), cultural perception of child quantity (χ2=26.373, p=0.000), decision maker for family planning (χ2=19.745, p=0.000) and discussion with partner (χ2=55.063, p=0.000). Conclusions: In Turkana County, Kenya, socio-cultural factors seem to significantly shape modern contraceptive choices among women of reproductive age. Religious beliefs, misconceptions, and gender preferences influence decisions. Cultural norms impact family size views, and autonomy prevails. Tailored interventions addressing these issues are crucial for better reproductive health outcomes.